Epoxidation of Hybrid Oleic Acid Derived From Palm Oil and Waste Cooking Oil For Eco-friendly Polyol Production - Azmi, Intan Suhada; Hamid, Nursyafiqah Nabihah; Jalil, Mohd Jumain (Recent Innovations in Chemical Engineering, 2025)
BackgroundPalm oil and waste cooking oil undergo functionalization by introducing epoxy groups onto their double bonds, which are subsequently opened to yield hydroxyl groups.ObjectivesThe objective of this paper is to produce epoxidized hybrid oleic acid with an applied heterogeneous catalyst for polyol feedstock.MethodsIn situ peracids are generated during the reaction by mixing an acid (commonly acetic acid or formic acid) with hydrogen peroxide. Range Kutta 4th Order Method of numerical integration was used to develop kinetic modeling for reaction based on the mathematical model.ResultsAfter 40 minutes of epoxidation reaction, the relative conversion to the oxirane percentage reached its maximum of 51%. Fourier transform infrared spectroscopy detected an absorption peak at 3300 cm-1, suggesting the presence of a hydroxyl group.ConclusionEpoxidation of palm oil and waste cooking oil using in situ peracids is an efficient method for converting unsaturated fatty acids into epoxidized oils, which have significant industrial applications.
Keywords: kinetic model